1. Clean, Green, Ethical (CGE) Management: What Research Do We Really Need? - Graeme B Martin; Teuku Reza Ferasyi (The Faculty of Veterinary Medicine of Syiah Kuala University, 2016)
Industries based on small ruminants are major contributors to world food supply but, in many production systems, reproductive technology is not directly relevant. In addition, there is a general need to embrace the vision for products that are ‘clean, green and ethical’ (CGE). In the concept of CGE management, the environment of the animal is used to control reproduction rather than technological tools. Nutrition is the primary factor but, rather than feeding ruminants with potential human food, we need to focus on forages with occasional ‘smart supplements’. This focus also opens up opportunities – new forages can supply energy and protein whilst improving animal health and welfare, and reducing carbon emissions.Nutritional inputs must be accurately coordinated with reproductive events to ensure that the metabolic signals are appropriate to the stage of the reproductive process. To control the timing of reproduction, we begin with simply managing the presence of the male but then seek more precision through the greater use of ultrasound.Finally, genetic improvement should be part of every industry strategy and it is critical in the long-term development of CGE management. Most aspects of CGE management have a strong genetic component, as evidenced by variation among genotypes, and among individuals within genotypes. For example, a combination of nutritional management with genetic improvement in the rate of muscle accumulation can accelerate sexual maturity, potentially leading to simultaneous improvements in meat production, reproductive efficiency and environmental footprint.For each local situation, we need to introduce the various elements of the CGE package in stages, adapting the process to cover variations in genotype and in geographical and socio-economic environments. Some concepts might need further research and development for local conditions. Ultimately, CGE management is a simple and cost-effective way to improve productivity whilst safeguarding the future of the livestock industries.